Влияние эксплуатационных факторов на показатели надежности вертолетных двигателей - Иленко, Е. Ю. (НТУ "ХПИ", 2009)
The impact of operational factors on reliability indices of GTD-350 helicopter engines has been established. The results have been obtained based on the general pattern of the effect of operational factors on reliability indices of aircraft engines as well as failure data for GTD-350 engines that have been operated in training flying units for 11 years.
Keywords: авиационные двигатели; надежность; вертолет; двигатель ГТД-350